Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.epsl.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Warmer and wetter or warmer and dryer? Observed versus simulated covariability of Holocene temperature and rainfall in Asia

Abstract: Temperatures in Asia, and globally, are very likely to increase with greenhouse gas emissions, but future projections of rainfall are far more uncertain. Here we investigate the linkage between temperature and precipitation in Asia on interannual to multicentennial timescales using instrumental data, late Holocene paleoclimate proxy data and climate model simulations. We find that in the instrumental and proxy data, the relationship between temperature and precipitation is timescale-dependent. While on annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 51 publications
(72 reference statements)
1
20
0
1
Order By: Relevance
“…We assume spatially homogeneous climatic trends across the CEL because modern short-term climatic events show strong spatial coherence (Merz et al, 2018;Rust et al, 2018) and long-term (i.e., millennial-scale) climate models and available land-cover data do not suggest a spatial heterogeneity of natural trends between adjacent regions. This assumption is limited by some constraints: first, available climate proxy data is heterogeneous concerning archive type, temporal coverage, and the type and spatiotemporal extent of the proxy-climate relationship (Mauri et al, 2015;Salonen et al, 2012;Väliranta et al, 2015); second, we lack comparable and independent syntheses of climate-proxy and land cover data on similar spatiotemporal scales (Marquer et al, 2017;Trondman et al, 2015); and third, the analyzed climate model output only provides larger-scale trends based on the first-order effects of CO2 and orbital forcing (Rehfeld and Laepple, 2016;Zhang et al, 2017) and does not consider regional climate-land cover feedbacks (Qian et al, 2015).…”
Section: Natural Burning Conditionsmentioning
confidence: 99%
“…We assume spatially homogeneous climatic trends across the CEL because modern short-term climatic events show strong spatial coherence (Merz et al, 2018;Rust et al, 2018) and long-term (i.e., millennial-scale) climate models and available land-cover data do not suggest a spatial heterogeneity of natural trends between adjacent regions. This assumption is limited by some constraints: first, available climate proxy data is heterogeneous concerning archive type, temporal coverage, and the type and spatiotemporal extent of the proxy-climate relationship (Mauri et al, 2015;Salonen et al, 2012;Väliranta et al, 2015); second, we lack comparable and independent syntheses of climate-proxy and land cover data on similar spatiotemporal scales (Marquer et al, 2017;Trondman et al, 2015); and third, the analyzed climate model output only provides larger-scale trends based on the first-order effects of CO2 and orbital forcing (Rehfeld and Laepple, 2016;Zhang et al, 2017) and does not consider regional climate-land cover feedbacks (Qian et al, 2015).…”
Section: Natural Burning Conditionsmentioning
confidence: 99%
“…Increasing evidence suggests that the model-based paradigm of 'wet-gets-wetter and dry-gets-drier' in a warmer world (Trenberth et al 2003, Held andSoden 2006) may be too simplistic (Sheffield et al 2012, Greve et al 2014, Byrne and O'Gorman 2015, Burls and Fedorov 2017. At the same time, evidence for a timescale-dependence of temperature-hydroclimate relationships is emerging (Rehfeld and Laepple 2016), but instrumental observations are too short to derive robust co-variations at longer timescales (Seftigen et al 2017). The elusive key to clarifying these relationships lies in understanding how temperature relates to precipitation, evapotranspiration and drought on multiple spatiotemporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al (2016) found that hydroclimate patterns have varied considerably between different warm periods in eastern China over the past 2000 years. Rehfeld and Laepple (2016) found that the linkage between temperature and precipitation over Asia is timescale dependent, and that model simulations agree with proxy data on shorter timescales but disagree on longer timescales. these results, together with the Northern Hemispheric proxy-model comparison by Ljungqvist et al (2016), indicate that the hydroclimate responses to low-frequency temperature changes are not yet sufficiently well known.…”
mentioning
confidence: 83%
“…F. C. Ljungqvist opened the workshop by presenting the research background and a suggested outline for a proposed contribution to Climate of the Past. In this context, two recent studies by Hao et al (2016) and Rehfeld and Laepple (2016) of East Asia were highlighted. Hao et al (2016) found that hydroclimate patterns have varied considerably between different warm periods in eastern China over the past 2000 years.…”
mentioning
confidence: 99%